The Effect of the Set System Method on the Physical Condition of Pencak Silat Athletes in Benteng Persada Pencak Silat College Athletes - Carmudi, Carmudi; Wahyuni, Dewi; Suganda, Mikkey Anggara (Jurnal Ilmu Keolahragaan, 2022)
Abstract _______________________________________________________ Physical condition is an important factor that supports the optimal performance of pencak silat athletes in facing the intensity of training and competition. Therefore, effective exercise methods are needed to improve the overall physical condition component. This study aims to determine the effect of the set system training method on improving the physical condition of pencak silat athletes, especially on endurance (VO₂max), muscle strength, speed, and agility. The research method used was pre-experimental with a one group pretest-posttest design. The research subjects amounted to 14 athletes from the Benteng Persada Pencak Silat College who underwent a set system training program for eight weeks (three times per week, a total of 24 sessions). Measurement instruments include bleep tests for VO₂max, push-ups, sit-ups, and squat jumps for muscle strength, as well as shuttle runs for speed and agility. Data analysis was carried out by paired t-test using SPSS Statistics 25. The results showed a significant increase in all physical variables: VO₂max increased from 41.05 to 44.96 ml/kg/min; push-ups from 42.36 to 57.5 times; sit-ups from 27 to 33.21 times; squat jump from 30.43 to 33.43 cm; and shuttle run improved from 13.84 to 12.13 seconds. The conclusion of this study is that the set system method has been proven to be effective in improving the physical condition of pencak silat athletes as a whole. These findings contribute to the development of structured and applicable physical training programs for pencak silat trainers and organizations.